THE IMPLEMENTATION OF SOVEREIGN IMMUNITY OF WARSHIPS TO UNMANNED UNDERWATER VEHICLES (UUV) UNDER LAW OF THE SEA - Naomi Catherine Felencia; R. Achmad Gusman Catur Siswandi; Imam Mulyana (International Law Department, Faculty of Law Universitas Padjadjaran, 2022)
Along with the times, there have been advances in marine technology which includes Unmanned Underwater Vehicles (UUV). Some countries have started using UUVs for both commercial and military marine activities since UUVs have several advantages that ordinary ships do not have. However, the development and application of UUVs for marine purposes raises numerous problems since there isn’t clear regulation regarding UUV. Current legal instruments only explain the meaning of ship without classifying the type of ship itself. It raises a problem since it led to different interpretations between countries and the determination of legal rules for UUV. One incident related to UUV technology can be seen from the Bowditch incident where from this incident there are differences in interpretation on the classification of UUV between America and Tiongkok. Other incidents can also be seen from the entry of foreign UUVs into Indonesia waters for research purposes. From several incidents, there are main issues to the classification of UUVs which are connected to warships and their military activities. The classification of UUVs as merchant ships or warships is necessary considering that the rights of immunity owned by warships will affect the legal status of UUVs and their activities. Regulations that are still ambiguous will affect the Coastal State’s actions if there are foreign UUVs entering their sea areas, especially if the UUVs are used for military activities. Therefore, it is necessary to have clear regulations regarding UUVs including their classification and determine marine activities that allowed for the use of UUVs.